Control effect of root exudates from mycorrhizal watermelon seedlings on Fusarium wilt and the bacterial community in continuously cropped soil - Li, Wei; Hu, Xue-Yi; Zhu, Cheng-Shang; Guo, Shao Xia; Li, Min (Frontiers in Plant Science, 2023)
Watermelon (Citrullus lanatus) is susceptible to wilt disease caused by Fusarium oxysporum f. sp niveum (FON). AMF colonization alleviates watermelon wilt and regulates the composition of root exudates, but the effects of mycorrhizal watermelon root exudates on watermelon Fusarium wilt is not well understood. Root exudates of watermelon inoculated with AMF (Funeliformis mosseae or Glomus versiformme) were collected in this study. Then the root exudates of control plants and mycorrhizal plants were used to irrigate watermelon in continuous cropping soil, respectively. Meanwhile, the watermelon growth, antioxidant enzyme activity, rhizosphere soil enzyme activities and bacterial community composition, as well as the control effect on FON were analyzed. The results indicated that mycorrhizal watermelon root exudates promoted the growth of watermelon seedlings and increased soil enzyme activities, actinomyces, and the quantity of bacteria in rhizosphere soil. The proportion of Proteobacteria and Bacteroides was decreased, and the proportion of Actinobacteria, Firmicutes, and Chloroflexi in rhizosphere soil was increased when the seedlings were watered with high concentrations of mycorrhizal root exudates. The dominant bacterial genera in rhizosphere soil were Kaistobacter, Rhodanobacter, Thermomonas, Devosia, and Bacillus. The root exudates of mycorrhizal watermelon could reduce the disease index of Fusarium wilt by 6.7–30%, and five ml/L of watermelon root exudates inoculated with F. mosseae had the strongest inhibitory effect on watermelon Fusarium wilt. Our results suggest mycorrhizal watermelon root exudates changed the composition of bacteria and soil enzyme activities in rhizosphere soil, which increase the resistance of watermelon to Fusarium wilt and promoted the growth of plants in continuous cropping soil.